RELATIONSHIP BETWEEN WEIGHT AND HEIGHT TO JUMP RESULTS IN EARLY AGE LONG JUMP ATHLETES FOSTERED BY PASI, ACEH BESAR REGENCY - Didi Yudha Pranata (Jurnal Ilmiah Teunuleh, 2022)
Athletics is the oldest sport in the world. Athletics has 4 numbers, namely running, walking, jumping and throwing numbers. Jump numbers have elements of physical conditions that must be owned by athletes, such as height and weight. The long jump is a sport that combines speed, strength, flexibility, endurance and accuracy in an effort to get as far as possible. Speed ??and strong leg muscles are also related to weight and height, because in the long jump the legs get a big load in the jump. Against the background of people's assumptions which state that differences in a person's body posture or weight and height affect the jump results, this research was conducted. In this study, a correlational research design was used which aims to determine the tendency of the existence or absence of correlation between variables. This correlational research was conducted to find out how much strength the relationship between the variables to be studied was. With the research subjects 7 Early Long Jump Athletes fostered by Pasi Aceh Besar District, so that in this study there were two variables, namely the dependent variable and the independent variable. Assuming H0: there is no relationship between weight and height and with jumps. H1: there is a relationship between weight and height with jumps. The research instruments used were of two kinds, namely instruments and test instruments. The research conducted will produce data in the form of ratio data, then the collected data is analyzed through inferential statistics in the form of simple, multiple regression analysis, and correlation analysis techniques. Based on the results of data analysis carried out, three conclusions were obtained as follows. First, with the results of H0 being rejected and H1 being accepted, there is a negative relationship between body weight and the long jump, which means that the heavier the weight, the shorter the long jump. The magnitude of the effect of body weight on the jump is 0.486 or 48.6%. Second, because H0 is rejected and H1 is accepted, there is a relationship between height and jump. The magnitude of the effect of height on the jump is 0.743 or 74.3%. Third, Based on the calculation, the correlation between weight and height combined has a relationship with jumps. The magnitude of the relationship is 61.45%. The conclusion is that for each sport it is necessary to pay attention to the body composition of the athlete in order to produce maximum results.